2008
DOI: 10.1177/0003319707306218
|View full text |Cite
|
Sign up to set email alerts
|

The Right Atrial Thrombus: The Sword of Damocles With Real Risk of Massive Pulmonary Embolism

Abstract: patients have a high incidence of massive pulmonary embolism with high mortality rate (from 29% to 100%), higher than the 8% to 10% of pulmonary embolism in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The effect of thrombolytic therapy on mortality is controversial. There are favorable results of thrombolytic therapy over heparin in patients with RHT associated PE in a small case series (10,13,(16)(17)(18)(19). First meta-analysis including 119 patients with RHT showed similar efficacy of all three treatment options (8).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The effect of thrombolytic therapy on mortality is controversial. There are favorable results of thrombolytic therapy over heparin in patients with RHT associated PE in a small case series (10,13,(16)(17)(18)(19). First meta-analysis including 119 patients with RHT showed similar efficacy of all three treatment options (8).…”
Section: Discussionmentioning
confidence: 97%
“…However a meta-analysis carried out by Rose et al (9) showed lower mortality rate (28.6 %). Kirin et al (13) reported six cases of RHT and two patients received heparin alone died. Whereas, they reported that the rest of four patients survived after thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Type B thrombi are nonmobile adherent thrombi formed by stasis due to decompensated heart disease (congenital or acquired) or to an indwelling foreign body (eg, catheter or pacemaker wire). 3 Type A thrombi, due to their high mobility, are lifethreatening when associated with an acute, symptomatic PE and have a mortality rate of 42%. A PE caused by type B thrombi occurs 40% of the time and usually is not fatal.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2] Right heart thrombi are the source of a PE less than 10% of the time; however, patients with a mobile right heart thrombus have mortality between 21% and 44%. 3 Patients with intravascular foreign bodies, including transvenous pacing wires, are at increased risk for developing right heart thrombi. 4,5 Current treatment recommendations for acute symptomatic PE suggest systemic thrombolytic therapy accelerates resolution of PE and results in rapid hemodynamic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…11 For these reasons, we performed emergency surgical thrombectomy. Although all the thrombi were completely removed and the patient was medicated with Coumadin postoperatively, potentially thrombogenic factors such as AF and severe LV dysfunction remained unchanged after surgery.…”
Section: Images In Cardiovascular Medicine Triple-chamber Cardiac Thrmentioning
confidence: 99%